1981
DOI: 10.1159/000182118
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Function in Hemodialyzed Patients with Cardiomegaly

Abstract: Left ventricular function was investigated in 21 chronic hemodialysis patients with cardiomegaly not due to major pericardial effusion. Angiographic and hemodynamic studies were performed in all, and selective coronary angiography in 16 patients. 5 patients had a history of long-standing arterial hypertension, 5 had clinical evidence of coronary artery disease, 3 had an overfunctioning arteriovenous fistula, and 3 had valvular heart disease. In 10 patients progressive cardiac failure developed without any appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Uremic cardiomyopathy was manifested as systolic dysfunction, concentric LV hypertrophy, or LV dilatation by echocardiogrophic evaluation, the most significant predictor of the development of cardiac failure and mortality being systolic dysfunction. 2,3 Many investigators have reported that a significant number of dialysis patients may have the echocardiographic features of congestive cardiomyopathy, 19,[20][21][22][23] and that LV hypertrophy is common in these patients. [22][23][24][25][26][27] According to one report, more than half of all patients on maintenance hemodialysis without any apparent coronary artery disease, pericardial effusion, valvular heart disease, or heart failure, had abnormal left ventricular function, and the significant abnormalities were enlargement of the left ventricular cavity, a reduction of myocardial contractility, and thickening of the left ventricular posterior wall.…”
Section: Discussionmentioning
confidence: 99%
“…Uremic cardiomyopathy was manifested as systolic dysfunction, concentric LV hypertrophy, or LV dilatation by echocardiogrophic evaluation, the most significant predictor of the development of cardiac failure and mortality being systolic dysfunction. 2,3 Many investigators have reported that a significant number of dialysis patients may have the echocardiographic features of congestive cardiomyopathy, 19,[20][21][22][23] and that LV hypertrophy is common in these patients. [22][23][24][25][26][27] According to one report, more than half of all patients on maintenance hemodialysis without any apparent coronary artery disease, pericardial effusion, valvular heart disease, or heart failure, had abnormal left ventricular function, and the significant abnormalities were enlargement of the left ventricular cavity, a reduction of myocardial contractility, and thickening of the left ventricular posterior wall.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that hemodialysis produces an improvement in left ventricular (LV) systolic function (10): an increase in LV contractility and a decrease in left ventricular end-diastolic volume and stroke volume. However, the improvement in LV systolic function depends on predialysis LV volume and systolic function; hemodialysis induces an increase in LV ejection fraction in patients with a reduced ejection fraction prior to dialysis but not in those with a normal predialysis ejection fraction (1 1).…”
Section: Cardiovascular System In Uremic Patients and Effects Of Hemomentioning
confidence: 99%
“…Congestive heart failure is a common complication in chronic hemodialysis patients [1,2], The cardiac perfor mance in uremia is clinically characterized by an inade quate left ventricular hypertrophy and a reduced diastolic compliance [3], Echocardiographic examinations demon strated a dilatation of the left ventricular internal diameter and a diminished fractional fiber shortening [4], Addition ally, an increase in left ventricular end-diastolic and endsystolic volumes as well as a reduction of myocardial con tractility and a decrease in left ventricular ejection fraction was described in patients with end-stage renal disease [5], Moreover, the hemodynamic state of chronic hemodialysis patients is characterized by an elevated cardiac output, an increased systemic vascular resistance, an elevated mean arterial pressure and an increased intravascular volume [6,7], Many factors chronically disturbed in renal failure may contribute to the complex cardiac findings: anemia [8], chronic fluid and volume overload, arterial hypertension, arteriovenous shunting of blood, episodic extracorporeal circulation, and increased cardiac work load. Alterations in the inotropic state of the heart induced by arrhythmias [9], myocardial damage based on coronary artery disease [10] or induced by metabolic and electrolyte imbalances are pos sibly involved in the pathogenesis of cardiac dysfunction in end-stage renal failure [1,11].…”
Section: Introductionmentioning
confidence: 99%